2014
DOI: 10.1177/1541931214581455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobile Technology Use on Walking

Abstract: Objective: The goal of this study was to evaluate the efficacy of combining cognitive and kinematic measurements to study the effects of mobile technology use on walking. Background: It has previously been shown that being distracted by a cell phone, or other mobile technology, can have a negative impact on activities such as crossing a street and may also alter gait patterns. While the negative effects of cell phone use on driving have been extensively studied, research into the distracted pedestrian is lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The common parameters in the reviewed studies are: gait phase [16], gait velocity [6,16], gait speed [14,[17][18][19], gait cycle [17], cadence [12,14,17,18], stride velocity [12], stride time [12,14,17], stride length [12,14,17,18,20], step time [14,17,21], step length [14,17,21,22], single support [17], and double support [17,18,22]. Other than the common parameters, the reviewed studies also used the other gait parameters: range of motion [20,23], local stability and margin of stability [21].…”
Section: Primary Task Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The common parameters in the reviewed studies are: gait phase [16], gait velocity [6,16], gait speed [14,[17][18][19], gait cycle [17], cadence [12,14,17,18], stride velocity [12], stride time [12,14,17], stride length [12,14,17,18,20], step time [14,17,21], step length [14,17,21,22], single support [17], and double support [17,18,22]. Other than the common parameters, the reviewed studies also used the other gait parameters: range of motion [20,23], local stability and margin of stability [21].…”
Section: Primary Task Performancementioning
confidence: 99%
“…Phoning is considered to be as distracting as a mental task [5], but less distracting than texting. The subjects walked slower and had shorter strides while performing walking and texting [12]. Texting involves reading and typing, which is more cognitively demanding than talking [11].…”
Section: Research Studies On Distracted Pedestriansmentioning
confidence: 99%
“…Furthermore, stride length was shorter while typing a text message on smartphones and tablets. Previous studies that tested the effects of walking while typing a text message on smartphones found that stride length was also reduced [7][8][9]. Comparing the step time indicated that the right step time was significantly different; the right step time was increased.…”
Section: Discussionmentioning
confidence: 87%
“…Most individuals who use smartphones and tablets develop addictive behaviors, impacting their use in the ADLs, especially when walking on such pavements as sidewalks and roads. This issue increases the risk of falling; crashing with obstacles or other passengers, and experiencing car accidents that may cause injury and death [3,7]. Numerous researchers are interested in exploring the use of smartphones while walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation